Comparison of Demographic Characteristics of Methamphetamine versus Opioid Users in The Addiction Treatment Center: A Case Study - Mahdieh Ebrahiminia; Maryam Ebrahiminia; Monire Azizi (Kerman University of Medical Sciences, 2017)
Background & Objectives: Opioid use has a long history in Iran. In recent years, with the changing pattern of drug use from traditional to industrial substances, the use of stimulants, especially methamphetamine has been increased. The aim of this study was to compare the demographic characteristics of methamphetamine and opioid users in a selected addiction treatment center in Zahedan city. Methods: This research was a cross-sectional descriptive-analytic study that was done in the period from April to March 2015 on the record of 156 users of methamphetamine or opioids referred to the selected addiction treatment center in Zahedan. The required information was collected from patients' records. Data analysis was done using chi-square and logistic regression and through SPSS software (version 21). Results: Most of the participants were male (89.7%), less than 35 years (50.6%), married (59%), employed (60.3%), illiterate or with primary education (35.9%). In terms of age, methamphetamine users were significantly younger than opioid users (P=0.004). The two groups did not have a significant difference in terms of gender (P =0.15), education level (P= 0.6) and marital status (P=0.94). In addition, in terms of job status, the majority of methamphetamine users, unlike opioid users, were unemployed (P = 0.01). Conclusion: The findings of this study showed that use of methamphetamine, in comparison to opioid, is more prevalent in younger and unemployed people; therefore, through promoting cultural and educational opportunities for youths, this kind of problems can be prevented. Keywords: Demographic characteristics, Methamphetamine, Opioid, addiction treatment center, Users Citation: Ebrahiminia M, Ebrahiminia M, Azizi M. Comparison of Demographic Characteristics of Methamphetamine versus Opioid Users in an Addiction Treatment Center: A Case Study. Journal of Health Based Research 2017; 3(1): 13-24.